Fulminant hepatic failure: a Portuguese experience - Areia, M (2012)
BACKGROUND: Fulminant hepatic failure (FHF) is a rare condition. Several series have been reported either by individual centres or in multicentre studies but, to our knowledge, this is the first report from a Portuguese population and might be a good example of FHF cases in a SouthWestern European population. AIMS: To present the experience in FHF of a Portuguese Hepatogastroenterological Intensive Care Unit. MATERIALS AND METHODS: Retrospective study of 61 cases of FHF consecutively admitted between February 1992 and October 2006. Definition and classification of FHF were those suggested by Trey and Davidson (1970) and O'Grady et al. (1993), respectively. Criteria and contraindications for hepatic transplantation (HT) were those proposed by Bernuau et al. (1991) and Muñoz (1993), respectively. RESULTS: Fifty-seven per cent of patients were women and median age was 37 years (range: 8-73). Most common cause of FHF was indeterminate (26%) followed by viral (23%) and drug-induced (23%), with 51% of cases with a hyperacute evolution. Global HT rate was 54% with criteria for HT present in 87% of the patients resulting in an applicability rate of 62%. Overall survival was 69% and transplant-free survival was 15%; transplanted patients had survival rates of 70 and 68% at 6 and 12 months, respectively. CONCLUSIONS: Drug-induced and viral agents were responsible for almost half of FHF cases with a clear predominance of hyperacute presentation. The HT rate was 54% and the applicability rate was 62%. The overall 1 year survival of 69% might reflect the adequacy of the HT criteria used.